2017
DOI: 10.1109/tac.2016.2601148
|View full text |Cite
|
Sign up to set email alerts
|

Semidefinite Programming Approach to Gaussian Sequential Rate-Distortion Trade-Offs

Abstract: Abstract-Sequential rate-distortion (SRD) theory provides a framework for studying the fundamental trade-off between datarate and data-quality in real-time communication systems. In this paper, we consider the SRD problem for multi-dimensional timevarying Gauss-Markov processes under mean-square distortion criteria. We first revisit the sensor-estimator separation principle, which asserts that considered SRD problem is equivalent to a joint sensor and estimator design problem in which data-rate of the sensor o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
130
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(131 citation statements)
references
References 52 publications
1
130
0
Order By: Relevance
“…Notably, the authors of [7] have * Laboratory for Information and Decision Systems, Massachusetts Institute of Technology (Email: ttanaka@mit.edu). This work provides a theoretical support of Section VI-B in [1]. This research was supported by JSPS postdoctoral fellowship.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…Notably, the authors of [7] have * Laboratory for Information and Decision Systems, Massachusetts Institute of Technology (Email: ttanaka@mit.edu). This work provides a theoretical support of Section VI-B in [1]. This research was supported by JSPS postdoctoral fellowship.…”
Section: Introductionmentioning
confidence: 58%
“…Suppose there exists a test channel ⊗ t∈N q(dz t |x t , z t−1 ) ∈ π L satisfying the constraint (2b) such that the corresponding 3 In [1], symbols r and s are used in place of p G and q.…”
Section: Existence Of Optimal Test Channel With Finite Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…Derpich and Østergaard in [5] considered variants of NRDF for stationary scalar-valued Gaussian autoregressive models of any order with pointwise MSE distortion fidelity and computed the asymptotic expression of the Gaussian NRDF for stationary scalar-valued Gaussian AR(1) sources which was first derived in [17,Equation (1.43)] using alternative methods. Tanaka et al in [19] revisited the finite-time NRDF for vector-valued Gauss-Markov sources with pointwise MSE distortion fidelity following the line of work of [8] and showed that the resulting optimization problem is semidefinite representable, thus, it can be solved numerically. However, none of the previously discussed works, i.e., [5], [8], [18], [19] provide a realization of the test channel conditional distribution that achieves the NRDF or attempt to identify the parameters in the realization given in [17,Theorem 5].…”
Section: Introductionmentioning
confidence: 99%